2021
DOI: 10.1103/physrevfluids.6.044612
|View full text |Cite
|
Sign up to set email alerts
|

Near-field coherent structures in circular and fractal orifice jets

Abstract: To investigate the influence of the orifice geometry on near-field coherent structures in a jet, Fourier proper orthogonal decomposition (Fourier-POD) is applied. Velocity and vorticity snapshots obtained from tomographic particle image velocimetry at the downstream distance of two equivalent orifice diameters are analyzed. Jets issuing from a circular orifice and from a fractal orifice are examined, where the fractal geometry is obtained from a repeating fractal pattern applied to a base square shape. While i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…We find that the lift-up mechanism is active in turbulent wakes, similar to wall-bounded shear flows (Abreu et al 2020) and turbulent jets (Nogueira et al 2019;Lasagna et al 2021). Conditional averaging and SPOD analysis demonstrate clearly that streamwise vortices lift up low-speed fluid from the wake's core and push down high-speed fluid from the outer wake.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…We find that the lift-up mechanism is active in turbulent wakes, similar to wall-bounded shear flows (Abreu et al 2020) and turbulent jets (Nogueira et al 2019;Lasagna et al 2021). Conditional averaging and SPOD analysis demonstrate clearly that streamwise vortices lift up low-speed fluid from the wake's core and push down high-speed fluid from the outer wake.…”
Section: Discussionmentioning
confidence: 66%
“…2019; Lasagna et al. 2021). Conditional averaging and SPOD analysis demonstrate clearly that streamwise vortices lift up low-speed fluid from the wake's core and push down high-speed fluid from the outer wake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commendable efforts have been directed to the understanding of relationship between the dominant structural modes in the flow. For example, works utilizing POD (Glauser and George 1987;Citriniti and George 2000;Jung et al 2004;Tinney et al 2008;Lasagna et al 2021) revealed that "volcano-like" and short-duration eruptions of high-strain turbulent flow co-exist with the streamwise vortices and that they are most intense after the collapse of the potential core. Other works have also confirmed through correlation-based techniques that the shear layer comprises long streaky structures and series of toroidal shear-layer vortices in the outer regions of the jet (Iqbal and Thomas 2007;Nogueira et al 2019;Samie et al 2021).…”
Section: Coherent Flow Structures In Turbulent Jetsmentioning
confidence: 99%